Asia in the Middle East: The Internationalization of Singapore Private Firms into the GCC - YEOH, Caroline (Institutional Knowledge at Singapore Management University, 2012)
Internationalization efforts into the GCC as a national initiative tend to be spearheaded by a vanguard of government-linked companies (GLCs), usually assisted in their entry through various connections, political or otherwise. As large companies with the presumed reliability of government backing, these GLCs tend to be involved in larger-scale, more critical, and more iconic projects. It is a matter of fact, however, that while internationalization may be led by large-scale and attention-grabbing GLCs, the vast majority of FDI and economic activity is, in the long term, entrenched in the activities of private companies. As such, it must logically follow that the study of these companies and their experiences in the Middle East must be of paramount relevance to assessing the state of internationalization into the region. In this paper, therefore, we focus the ambit of our continuing research into the internationalization efforts of Singapore into the Middle East onto several case studies of Singapore private firms in the GCC, and seek to derive observations pertinent both to the idiosyncrasies of Singapore business in the context of the Middle East, and conclusions pertinent to private firms across the globe with an interest in the region's rich yet cryptic business environments.